2008
DOI: 10.1677/jme-07-0175
|View full text |Cite
|
Sign up to set email alerts
|

C2C12 myoblastoma cell differentiation and proliferation is stimulated by androgens and associated with a modulation of myostatin and Pax7 expression

Abstract: Androgens are modulators of skeletal muscle adaptation and regeneration processes. The control of satellite cell activity is a key mechanism during this process. In this study, we analyzed the ability of dihydrotestosterone (DHT) and anabolic steroids to induce and modulate the differentiation of C2C12 myoblastoma cells toward myotubes. C2C12 cells were dose-dependently treated with DHT and anabolic steroids. The time-dependent effects on differentiation were measured and correlated with the expression of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 34 publications
2
40
0
2
Order By: Relevance
“…Testosterone can stimulate satellite cell proliferation (41), but its effects on differentiation are still unclear (17,20,113). The roles of estrogen in skeletal muscle are more pleiotropic and complex.…”
Section: Integration Of Signaling Pathways To Modulate Ups Function Imentioning
confidence: 99%
“…Testosterone can stimulate satellite cell proliferation (41), but its effects on differentiation are still unclear (17,20,113). The roles of estrogen in skeletal muscle are more pleiotropic and complex.…”
Section: Integration Of Signaling Pathways To Modulate Ups Function Imentioning
confidence: 99%
“…Adult skeletal muscle fibers are terminally differentiated, and muscle repair and hypertrophy can occur either through an increase in the number of myonuclei, via activation of satellite cells (muscle stem cells) to proliferate as myoblasts, differentiate into myotubes and fuse with myofibers, or via an increase in protein content of postproliferative myofibers. While some studies have shown that androgens increase myoblast proliferation rate and/or delay differentiation (Powers & Florini 1975, Doumit et al 1996, Sinha-Hikim et al 2006, Diel et al 2008, others suggest the predominant actions are on protein accretion in myofibers (Ferrando et al 1998, Chen et al 2008. Maximal hypertrophic response to muscle overloading requires myofiber AR, but also involves other target cells (Ferry et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another response to GDF8 treatment was the increased expression of Pax7 and Sox8. The down-regulation of Pax7 by constant MyoD expression is described to be the initial signal for differentiation of the cells (Diel et al 2008). All these transcriptomic changes indicate that GDF8-treated myoblasts did not reach the status of differentiated muscle cells.…”
Section: Discussionmentioning
confidence: 97%